White Blood Cell Count as a Predictor of Incident Type 2 Diabetes Mellitus Among Non-Obese Adults: A Longitudinal 10-Year Analysis of the Korean Genome and Epidemiology Study - Park JM; Lee HS; Park JY; Jung DH; Lee JW (Dove Medical Press, 2021)
Jae-Min Park,1,2 Hye Sun Lee,3 Ju-Young Park,4 Dong-Hyuk Jung,5 Ji-Won Lee1 1Department of Family Medicine, Yonsei University College of Medicine, Gangnam Severance Hospital, Seoul, Republic of Korea; 2Department of Medicine, Graduate School of Medicine, Yonsei University, Seoul, Republic of Korea; 3Biostatistics Collaboration Unit, Yonsei University College of Medicine, Seoul, Republic of Korea; 4Department of Statistics and Data Science, Yonsei University, Seoul, Republic of Korea; 5Department of Family Medicine, Yonsei University College of Medicine, Yongin Severance Hospital, Gyeonggi-do, Republic of KoreaCorrespondence: Ji-Won LeeDepartment of Family Medicine, Yonsei University College of Medicine, Gangnam Severance Hospital, 211 Eonju-ro, Gangnam-gu, Seoul, 06273, Republic of KoreaTel +82 2 2019 3482Fax +82 2 3462 8209Email indi5645@yuhs.acPurpose: Limited evidence is available on whether the white blood cell (WBC) count is a predictor of type 2 diabetes mellitus (T2DM) in non-obese individuals. This study aimed to determine whether WBC count could be used as an indicator for the prediction of incident T2DM among non-obese individuals using a large, community-based Korean cohort that was observed over 10 years.Patients and methods: A total of 4211 non-obese adults without diabetes aged 40– 69 years were selected from the Korean Genome and Epidemiology Study. The participants were divided into four groups according to WBC count quartiles. We prospectively assessed the hazard ratios (HRs) with 95% confidence intervals (CIs) for incident T2DM, based on the American Diabetes Association criteria, using multivariate Cox proportional hazards regression models over 10 years after the baseline survey.Results: During the follow-up period, 592 (14.1%) participants had newly developed T2DM. The higher quartile of WBC count groups showed significantly higher cumulative T2DM incidence over 10 years after the baseline survey (log-rank test, P < 0.001). Compared with the HRs for individuals in the referent lowest quartile, the HR (95% CI) for incident T2DM in individuals in the highest quartile was 1.55 (1.10– 2.18) after adjusting for confounding variables.Conclusion: A higher WBC count predicts future incident T2DM among community-dwelling non-obese Korean adults. This study suggests that WBC count could facilitate the prediction of non-obese individuals susceptible to T2DM.Keywords: white blood cell count, type 2 diabetes mellitus, chronic low-grade inflammation, non-obese adults